¿What is tense grammar for? - Zilberberg, Claude (2009)
The interesting question ¿What does tense grammar is for?, is answered by Claude Zilberberg with a reflection that captures its theories about tensivity and its function in the production of sense. After a clarification on “language and sense”, he raises the issues of tense grammar, starting with the construction of its own categories: intensity and extensity, mainly, as valences that define and determinate there own values; the interval that regulates the quantity problems; the syntax of intensity and syntax of extensity; to finish with the value problematic, which is always in the sight.